KAJIAN PERGESERAN KERJA WANITA DARl TENAGA PEMETIK TEH KE JEN1S PEKERJAAN LAINNYA (KASUS D1 DESA SEKITAR PERKEBUNAN TEH PT. SARANA MAND1RI MUKTI KABUPATEN KEPAHIANG) - Arianti, Nyayu Neti; Priyono, Basuki Sigit (Jurnal AGRISEP, 2010)
This research is aimed to investigate:  1) which jobs were chosen by women  who worked as the tea leaves pickers at P'I'Barana Mandiri  Mukti Plantation  in Kabupaten Kepahiang after they have fined due to the collapse of the plantation,  2)  the women's  working  time in their new job, 3) their income from their new job and 4) their income contribution  to their family income. The snowball sampling  was used to take the 60 respondents.  The primary  data were collected through interview and the secondary  data were taken from other institutions related to this research. The research results showed that there were 31J% respondents had new job as the helper of their husband  working  on their own farm, 20% worked  to clear weeds away at other tea plantation,  16J% as the pickers at other tea plantations  and 11,7% as housewives.  The women worked 4,8 hours/day on an average at their new job. The average of the women's  income from their new job was Rp 282.833,30/month  and their contribution to their family income was 35,96 on an average and it is classified on low category.